2017
DOI: 10.3390/geriatrics2040033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug-Disease Interactions and Their Association with Unplanned Hospital Readmission Utilizing STOPP Version 2 Criteria

Abstract: Abstract:Early hospital readmission is a common problem among geriatric patients, as they are more susceptible to adverse drug events, which are associated with increased hospital admission. The objective is to examine the association between exposure to potentially inappropriate medications under selected STOPP version 2 criteria related to drug-disease interactions and unplanned early hospitalization within 28 days of index admission in elderly patients prescribed a potentially inappropriate medication. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“… 22 Other observational studies have found consistent associations between the STOPP criteria and avoidable adverse drug events relevant to the index admission among hospital inpatients, 12 poorer quality of life, 14 emergency department visits, 14 15 and unplanned readmission to hospital. 23 Prescribing included in STOPP was considered causal in 30% of adverse drug reactions in a Swedish study in an older population, 24 and in a study of definitely or possibly avoidable adverse drug events that led to hospital admission, 62.2% were listed in the STOPP criteria. 12 On this basis, the STOPP criteria can be considered a valid process measure of quality of care, and they have been used as primary outcomes in interventional trials aiming to improve prescribing.…”
Section: Methodsmentioning
confidence: 99%
“… 22 Other observational studies have found consistent associations between the STOPP criteria and avoidable adverse drug events relevant to the index admission among hospital inpatients, 12 poorer quality of life, 14 emergency department visits, 14 15 and unplanned readmission to hospital. 23 Prescribing included in STOPP was considered causal in 30% of adverse drug reactions in a Swedish study in an older population, 24 and in a study of definitely or possibly avoidable adverse drug events that led to hospital admission, 62.2% were listed in the STOPP criteria. 12 On this basis, the STOPP criteria can be considered a valid process measure of quality of care, and they have been used as primary outcomes in interventional trials aiming to improve prescribing.…”
Section: Methodsmentioning
confidence: 99%
“…106 Also, it is debatable whether the health outcomes are due to the PIPs or the disease/condition itself. Several studies 38,62,68,69,76,79,84,86,87 failed to adjust for comorbidities. The heterogeneity in adjustment may be 1 of the factors why pooled estimates from the adjusted vs. unadjusted model vary in the magnitude/direction of effect, specifically for the outcome related to hospital readmissions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The coexisting medical condition of a patient has been shown to be associated with adverse drug events due to drug‐disease interaction 51 . For instance, the past/coexisting diseases of the cardiac system make the heart prone to the adverse hypokalaemic event 52 .…”
Section: Discussionmentioning
confidence: 99%